2019
DOI: 10.1186/s12933-019-0823-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential relation between soluble growth differentiation factor-15 and testosterone deficiency in male patients with coronary artery disease

Abstract: Background There is a mutual interaction between inflammation and endocrine disorders in the development of coronary artery disease (CAD). Growth differentiation factor-15 (GDF-15) is associated with CAD, and the effects of testosterone on CAD as reported in literature have been considered as anti-atherosclerotic. The present study aimed to examine the possible association between serum GDF-15 and testosterone in male CAD patients. Methods GDF-15 and testosterone concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Moreover, in prostate cancer cells, the upregulation of GDF-15 was directly affected by the downregulation of T and E2 [ 40 ]. Studies have shown that GDF-15 serum levels were negatively associated with T levels and the T/E2 ratio, and the combination of T and E2 could significantly reduce the GDF-15 level [ 41 , 42 ]. Based on the currently available literature, it can therefore be assumed that there is a regulatory interaction between serum GDF-15 and sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in prostate cancer cells, the upregulation of GDF-15 was directly affected by the downregulation of T and E2 [ 40 ]. Studies have shown that GDF-15 serum levels were negatively associated with T levels and the T/E2 ratio, and the combination of T and E2 could significantly reduce the GDF-15 level [ 41 , 42 ]. Based on the currently available literature, it can therefore be assumed that there is a regulatory interaction between serum GDF-15 and sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Serum GDF-15 levels were significantly and negatively associated with testosterone in patients with coronary artery disease or HBV-associated hepatocellular carcinoma. [28][29][30] Thus, the present research was to investigate the association among serum GDF-15 level and testosterone levels in depressive patients with or without suicidal ideation. Our data confirmed depressed subjects with suicidal ideation showed much higher serum GDF-15 levels than those without suicidal ideation, regardless of whether they had a testosterone <314 ng/dL or ≥314 ng/dL.…”
Section: Discussionmentioning
confidence: 99%
“…The results from previous studies have shown that increased circulating GDF15 levels were closely associated with the development and progression of various cardiovascular diseases (including myocardial ischaemia/reperfusion, heart failure, atherosclerosis, and acute coronary syndrome), and were shown to be a strong and independent predictor of mortality and disease progression in patients with atherosclerosis and coronary artery disease [5][6][7][8][9][10][31][32][33][34][35][36]. In diabetic patients, higher levels of lipids and chronic inflammation may directly damage the cardiovascular system [37].…”
Section: Discussionmentioning
confidence: 99%